The Impact of Yeast Genetics and Recombinant DNA Technology on the Wine Industry - A Review - Pretorius, L.S.; van der Westhuizen, T.J. (South African Journal of Enology and Viticulture, 2017)
Despite our limited knowledge of the genetic make-up of commercial wine yeasts and the fact thatthe advantages of genetic manipulation of wine yeasts have not yet been demonstrated in practice, the wine industry has to realise that "the name of the game" is recombinant DNA and that the pace of progress is fast. The technology is so powerful that it now enables manipulation of the genome in ways hard to imagine only a decade ago. In this review we highlight the importance of the wine yeast to the wine industry and the necessity for well-planned breeding programmes. First, we summarise reliable taxonomic methods that are useful as diagnostic techniques in such breeding strategies. Second, we emphasise the complexity of the genetic features of commercial wine-yeast strains. Third, we review the genetic techniques available and point out the potential of these techniques (individually and in combination) in strain-development programmes. Finally, we attempt to stimulate interest in the genetic engineering of wine yeasts by discussing a few potential targets of strain development. The impact of yeast genetics and recombinant DNA technology on the wine industry promises to be impressive.